2014
DOI: 10.1111/anu.12149
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of fishmeal by fish protein hydrolysate and biofloc in the diets ofLitopenaeus vannameipostlarvae

Abstract: This study aimed to evaluate the effect of the gradual replacement of fishmeal with fish protein hydrolysate (FPH) and biofloc flour (BF) in the diets of white shrimp Litopenaeus vannamei postlarvae (2 mg). Five diets (420 g kg À1 of crude protein) were formulated, and these replaced 0 (control), 10, 20, 30 and 40% (T0, T10, T20, T30 and T40, respectively) of the fishmeal. A commercial diet was used as an external control. The alternative ingredients FPH and BF were added at a ratio of 1 : 1. After 42 days, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 40 publications
1
21
0
6
Order By: Relevance
“…Biofloc system provides an available rich natural resource of protein‐lipid at any time (Avnimelech ) with highly diverse components (Martinez‐Cordova et al . ) consisting bacterial protein (Ballester, Abreu, Cavalli, Emerenciano, Abreu & Wasielesky ; Hargreaves ), poly‐β‐hydroxybutyrate created by bacteria (De Schryver, Sinha, Kunwar, Baruah & Verstraete ), microalgae, protozoa, nematodes (Azim, Little & Bron ; Valle, Jr, Silva, Bezerra, Correia, Peixoto & Soares ), copepods and rotifers (Ray, Lewis, Browdy & Leffler ) and diatoms, copepods and polychaetes (Porchas‐Cornejo, Martinez‐Cordova, Martinez‐Porchas, Barraza‐Guardado & Ramos‐Trujillo ). These natural products play an important role in recycling nutrients, improvement of growth performance and activity of digestive enzymes in shrimp (Xu & Pan ; Xu, Pan, Zhao & Huang ; Xu, Pan, Sun & Huang ).…”
Section: Discussionmentioning
confidence: 99%
“…Biofloc system provides an available rich natural resource of protein‐lipid at any time (Avnimelech ) with highly diverse components (Martinez‐Cordova et al . ) consisting bacterial protein (Ballester, Abreu, Cavalli, Emerenciano, Abreu & Wasielesky ; Hargreaves ), poly‐β‐hydroxybutyrate created by bacteria (De Schryver, Sinha, Kunwar, Baruah & Verstraete ), microalgae, protozoa, nematodes (Azim, Little & Bron ; Valle, Jr, Silva, Bezerra, Correia, Peixoto & Soares ), copepods and rotifers (Ray, Lewis, Browdy & Leffler ) and diatoms, copepods and polychaetes (Porchas‐Cornejo, Martinez‐Cordova, Martinez‐Porchas, Barraza‐Guardado & Ramos‐Trujillo ). These natural products play an important role in recycling nutrients, improvement of growth performance and activity of digestive enzymes in shrimp (Xu & Pan ; Xu, Pan, Zhao & Huang ; Xu, Pan, Sun & Huang ).…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, the higher growth performance of shrimp that were cultured in biofloc in comparison to the clear water group is in agreement with previous findings (Ray et al 2011;Irshad et al 2016). Valle et al (2015), replaced fish meal with biofloc flour and protein hydrolysate in the diet of L. vannamei and indicated that biofloc flour is a potential ingredient that can be used as substitute for fishmeal. In our study, whole-body proximate composition was not affected much by the FM substitution with SBM.…”
Section: Discussionmentioning
confidence: 99%
“…It is an ideal technology for converting low value by products into biologically functional products (Gildberg, ; Shahidi & Botta, ). Numerous studies found that plants and animals protein hydrolysates have been widely investigated in aquaculture (Aksnes, Hope, & Albrektsen, ; Aksnes, Hope, Hostmark, & Albrektsen, ; Cordovamurueta & Garciacarreno, ; Song et al., ; Valle et al., ). However, there is little information concerning enzymatic hydrolysate of defatted silkworm pupa (EHDSP) applied in aquatic animal culture.…”
Section: Introductionmentioning
confidence: 99%